Effect of tufting on the response of non crimp fabric composites. - Colin de Verdiere, Mathieu; Pickett, Anthony K.; Skordos, Alexandros A.; Witzel, Volker (Cranfield University, 2007)
This paper examines the effectiveness of tufting in enhancing the through the thickness properties of non crimped fabrics. The response of tufted and untufted carbon/epoxyn on crimped fabric composites produced using resin infusion is investigated in axial tension and compression and cyclic [±45] loading. The out- of-plane response is studied in mode I and mode II delamination tests. Tufted material has significantly higher delamination resistance and lower in plane properties in tension and compression. Tufted and untufted non crimp fabric composites have similar response in shearin terms of both plastic strain and strength. Optical strain measurements allowed monitoring of the two dimensional damage field incyclic experiments. Damage tends to be localised in untufted specimens, where as it becomes more uniform across the width of specimens with tufts. Material models for untufted and tufted non crimped fabric composites simulating both non-linear in-plane behaviour and delamination damage were developed. Material parameters were estimated from experimental results, and both material submodels were implemented in a commercial explicit finite element code which allows the in corporation of delamination behaviour using cohesive interface elements. A comparison of experiments and finite element model results simulating coupons verified the implementation of the models
Keywords: damage field; delamination; tufting; non crimp fabric; modelling; crash